Why should anyone work here? what it takes to create an authentic organization - Goffee, Robert 1952-; Jones, Gareth 1951- (Harvard Business Review Press, 2015)
"It used to be that businesses could ask individuals to conform to the organization's needs. But now leaders are charged with creating the best company on earth to work for: they must transform their organizations to attract the right people, keep them, and inspire them to do their best work. In Why Should Anyone Work Here? Rob Goffee and Gareth Jones identify the six key organizational attributes to do just that. In separate chapters, they delve deeply into each one: 1. Let people be themselves 2. Practice radical honesty 3. Magnify people's strengths 4. Stand for authenticity (more than shareholder value) 5. Make work meaningful 6. Make simple rules With vivid stories and examples, the authors illustrate the kind of strong, attractive workplace culture that leads to sustained high performance. They also provide ways of assessing how your company is doing, and describe the tensions and trade-offs that leaders must manage as they transform their organizations. Why Should Anyone Work Here? is the question all contemporary organizational leaders must constantly ask themselves if they want to survive and thrive in the new world. This is the book that will help them answer that question"...
Keywords: BUSINESS & ECONOMICS / Workplace Culture / bisacsh; BUSINESS & ECONOMICS / Leadership / bisacsh; BUSINESS & ECONOMICS / Management / bisacsh; Corporate culture; Organizational behavior; Leadership; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management